The Influence of the School Committee's Role on the Fulfillment of School Facilities and Infrastructure and the Quality of Educational Services - Pujianti, Meirita; Sirodj, Rusydi A.; Hidayat, Rais (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of the role of school committees on the fulfillment of facilities and infrastructure and the quality of educational services in public elementary schools in Dempo Utara District, Pagaralam City. Using a quantitative approach, this research employs a survey method through questionnaires distributed to principals, teachers, and school committee members. Data analysis results indicate that the role of school committees significantly influences the fulfillment of school facilities and infrastructure (p0.05). Moreover, the committee's role positively impacts the quality of educational services, particularly in the aspects of supervision and support for curriculum development. This study underscores the importance of collaboration between schools and communities through school committees to enhance education quality. Recommendations are directed to schools and the government to further empower school committees to optimize the quality of educational services.